The role of aromatase in breast cancer - Jarząbek, Katarzyna; Wołczyński, Sławomir (Menopause Review/Przegląd Menopauzalny, 2003)
The most of breast cancer in postmenopausal women is estrogen-dependent. The main question is which source of estrogen: estradiol circulating in the plasma or estradiol locally produced in extragonadal sites is a major factor stimulating the growth of the tumour. It seems that the local biosynthesis of estrogens in different tissues plays a crucial role in the development and growth of breast tumours and aromatase is a key enzyme regulating the local synthesis of estrogens. In our study we present recent concepts of the mechanisms activating aromatase and the role of aromatase in breast tissue and breast cancer.